Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Modeling regional ionospheric delay with ground-based BeiDou and GPS observations in China - Rui Zhang; Wei-wei Song; Yi-bin Yao; Chuang Shi; Yi-dong Lou; Wen-ting Yi (GPS Solutions, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells - Xin-ping Liang; Dong-qiang Zhang; Yan-yan Chen; Rui Guo; Jie Wang; Cheng-zhang Wang; Ying-hua Shi (Journal of Zhejiang University-SCIENCE B, 2015)

Effect of the CYP2D6 gene polymorphism on postoperative analgesia of tramadol in Han nationality nephrectomy patients - Hong Dong; Shu-jun Lu; Rui Zhang; Dong-dong Liu; Yan-zhuo Zhang; Chun-yu Song (European Journal of Clinical Pharmacology, 2015)

The effects of ENSO under negative AO phase on spring dust activity over northern China: an observational investigation - Yun Gon Lee; Jhoon Kim; Chang‐Hoi Ho; Soon‐Il An; Hi‐Ku Cho; Rui Mao; Baijun Tian; Dong Wu; Jae N. Lee; Olga Kalashnikova; Yunsoo Choi; Sang‐Wook Yeh (International Journal of Climatology, 2015)
The effects of El Niño/Southern Oscillation ( ENSO ) under negative Arctic Oscillation ( AO ) phase on the Asian dust activity are investigated for springs of the period 1961–2002. The spring dust index ( DI ) describing the monthly frequencies of three types of dust events (e.g. dust storm, blowing dust, and floating dust) exhibits a significant increase in the years of negative AO phase (hereafter AO −) and El Niño, compared with that in the years of AO − and La Niña. Averaged over all observation stations, the spring DI (49.7) during the El Niño/ AO − years is higher by 11.4% or 29.8% than that (38.3) during the La Niña/ AO − years. We suggest possible physical mechanism that the anomalous large‐scale environments associated with AO − and El Niño are more effective to provide favourable conditions to enhance Asian dust activity. During the El Niño/ AO − years, meridional gradients of pressure and temperature over the dust source regions are significantly enhanced by decreasing the geopotential height and warming air temperature that originated from the north and south of source regions, respectively, under the influence of AO − and El Niño. These also intensify the zonal wind shear and atmospheric baroclinicity, thereby producing enhanced cyclogenesis and dust occurrences over the major source regions. At the same time, dust transport paths with the stronger westerly winds are developed by the combined constraints of anomalous cyclone over the Siberia and the Mongolia and anomalous anticyclone over the western North Pacific, and thus strengthen dust transport to the downwind regions.

Evaluation of yeasts from Tibetan fermented products as agents for biocontrol of blue mold of Nashi pear fruits - Hao Hu; Yang Xu; Huang-ping Lu; Rui Xiao; Xiao-dong Zheng; Ting Yu (Journal of Zhejiang University-SCIENCE B, 2015)

Low Bone Mass is Associated with Stroke in Chinese Postmenopausal Women: The Chongqing Osteoporosis Study - Rui Zhou; Dong Liu; Rui Li; Shiming Zhou; Min Cui; Lin Chen; Huadong Zhou (Cell Biochemistry and Biophysics, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Chemical modification, characterization and bioactivity of a released exopolysaccharide (r-EPS1) from Lactobacillus plantarum 70810 - Kun Wang; Wei Li; Xin Rui; Teng Li; Xiaohong Chen; Mei Jiang; Mingsheng Dong (Glycoconjugate Journal, 2015)